1995
DOI: 10.1207/s15327949pac0104_7
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and assessing problem solving for international conflict resolution.

Abstract: Rationale and methodology for teaching a problem-solving approach to international conflict resolution in college courses and for assessing the outcomes of instruction are described in this article. The Conflict Resolution Strategies Checklist was developed to evaluate students' problem solving in essays about international conflict scenarios. Interrater reliability was adequate. Checklist scores correlated positively with Cornell Critical Thinking Test scores and were highest for students majoring in internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Previous studies using the earlier version of the checklist reported adequate interrater reliability and evidence for construct validity (Nelson et al, 1995). Checklist scores were sensitive to effects of instruction, were higher for students with an academic background in international relations, and were correlated with Cornell Test of Critical Thinking (Ennis, Millman, & Tomko, 1985) scores.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…Previous studies using the earlier version of the checklist reported adequate interrater reliability and evidence for construct validity (Nelson et al, 1995). Checklist scores were sensitive to effects of instruction, were higher for students with an academic background in international relations, and were correlated with Cornell Test of Critical Thinking (Ennis, Millman, & Tomko, 1985) scores.…”
Section: Methodsmentioning
confidence: 94%
“…For the score on generating alternatives, we allowed credit for either communication or negotiation, but not for both, because negotiation implies communication. Higher scores are indicative of better problem solving in accordance with the assumptions that quality of problem solving relates to the number of relevant analytical processes and issues addressed, the number of relevant action alternatives generated, and the number of relevant consequences and criteria considered in the evaluation of action alternatives (Nelson et al, 1995).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…University students in various classes who received instruction in problem solving for international conflict resolution were subsequently able to generate more conciliatory strategies for dealing with hypothetical international conflicts compared with control groups (Nelson, Golding, Drews, & Blazina, 1995). Courses dealing with international conflict issues, but not explicitly providing a prescriptive model for problem solving, did not significantly affect students’ problem-solving abilities.…”
Section: Evidence For Influence Of Person Factors On Peacefulnessmentioning
confidence: 99%